Manifestations of Cultural Systems in the Performance of the Theater Actor: The Play ”Ya Rab” as a Model - Jabar Jasib, Researcher. Maher; Abdul Hussein, Prof. Dr. Ali (Basra studies journal, 2024)
Culture is the backbone and the essential cornerstone of human societies. Naturally, the culture of one society differs from another due to its origins, interests, and the influence of its surrounding environment, along with various other systems that have permeated its social fabric, as well as its intellectual and social outputs. The focus of this research revolves around two key terms that significantly impact the actor’s performance through their influence: system and culture, and their effect on the theatrical actor’s performance. Scientific research has increasingly concerned itself with specific terms and concepts, striving to thoroughly understand and interpret them so they can be used precisely in their proper context, drawing upon scientific methods and references. Directing a term in the right direction allows for control over the knowledge that research aims to achieve. The production of cultural systems has taken on dimensions, implications, and representations that lead the audience to a different understanding, uncovering the codes of theatrical performance, deciphering its hidden meanings and symbols, and searching for its deeply embedded elements within the performance and the actor’s tools. These tools guide the performance along a defined or assumed path. The text is enriched by active and intentional symbolic movements, which take on a mental and conceptual role in their creation, defined as the cultural system. The actor then uses their tools to convey the meaning to the audience through an implicit system, possibly through movement or the actor’s language. Language is the medium through which the cultural system is transmitted, and our language—whether written or spoken—is subject to symbolic systems. These systems, in turn, subject the produced content to pressures and exert mechanisms of dominance, influencing the formation of the collective unconscious.